(untitled) (Journal of Universal Science Research, 2024)
The article analyzes specific trends of the ongoing reforms and transformations in Uzbekistan, implementation of the tasks indicated in The Strategy for Actions on the development of Uzbekistan in 2017-2024, in the context of development and liberalization of the economy. Thus, the article investigates practical measures to implement these tasks, changes in approaches towards the interaction of the state, population, business community, etc.